Polarization self-screening in [0001] oriented InGaN/GaN light-emitting diodes for improving the electron injection efficiency - Zhang, Zi-Hui (2015)
InGaN/GaN light-emitting diodes (LEDs) grown along the [0001] orientation inherit very strong polarization induced electric fields. This results in a reduced effective conduction band barrier height for the p-type AlGaN electron blocking layer (EBL) and makes the electron blocking effect relatively ineffective and the electron injection efficiency drops. Here, we show the concept of polarization self-screening for improving the electron injection efficiency. In this work, the proposed polarization self-screening effect was studied and proven through growing a p-type EBL with AlN composition partially graded along the [0001] orientation, which induces the bulk polarization charges. These bulk polarization charges are utilized to effectively self-screen the positive polarization induced interface charges located at the interface between the EBL and the last quantum barrier when designed properly. Using this approach, the electron leakage is suppressed and the LED performance is enhanced significantly.